A novel metal–organic framework based on hexanuclear Co(ii) clusters as an anode material for lithium-ion batteries. Issue 37 (4th September 2018) - He, Yuan-Chun; Yu, Yang; Wang, Lingyan; Yang, Jiaqin; Kan, Wei-Qiu; Yang, Yan; Fan, Yao-Yao; Jing, Zhihong; You, Jinmao
Abstract : A new metal–organic framework, [Co(L)]·1.5H2 O (1 ), has been successfully synthesized, where its electrochemical application has been investigated. Abstract : A new metal–organic framework, [Co(L)]·1.5H2 O (1 ), has been successfully synthesized from an organic ligand, 3-carboxy-1-(4′-carboxybenzyl)-2-oxidopyridinium. Compound1 displays a novel 3D framework with a capsule-shaped cavity and a hexanuclear [Co6 ] cluster. The temperature-dependent magnetic susceptibility of compound1 has been investigated. The electrochemical application of compound1 as a lithium-ion battery anode material was also explored. To improve the electrochemical performance of compound1, we utilized compound1 as a novel precursor to prepare a Co3 O4 @C composite. By comparison, the Co3 O4 @C composite shows a higher capacity and better cycling performance, which provides a new direction for the design of anode materials for lithium-ion batteries.